LAYANAN BIMBINGAN KELOMPOK DALAM PENGEMBANGAN SELF EFFICACY UNTUK MENENTUKAN KEPUTUSAN KARIR BAGI SISWA - Debi Agustin, Debi Agustin; Jumi Adela Wardiansyah, Jumi Adela Wardiansyah; Rofiqa Duri, Rofiqa Duri (Yayasan Darul Hasanah Aceh, 2024)
Career as a process that an individual wiil undergo must be planned well since school. Careful planning wiil make it easy for individuals to make decisions regarding their career. The obstacle that students lack self-efficacy/confidence in themselves to determine career decisions. It is hoped that this problem can be resolved through group guidance services. The aim of this research is to explain efforts to develop self-efficacy though group guidance services to help students determine their career decisions. This research is a type of field research (Field Research) with a qualitative research type and uses descriptive methods. The date source in this research comes from the guidance and counseling activity report book at SMKN 1 SIGLI. The analysis technique in this research is in thee stages, namely, date reduction, date presentation and drawing conclusions. Students who experience low self-afficacy in career planning are characterized by characterzed by characteristics such as, 1) indecisive in choosing a career plan, 2) not confident in their career choice, 3) lack of in-depth information obtained regarding caree panning. Group guidance services are carried out through 4 stages, such as the formation stage, transition stage, activity stage and final stage. The result of this group guidance in career service is that students no longer experience doubt and lack of confidence in career metters, obtain in-depth information about careers and can make quick and appropriate decisions about their career plans. This indicates that they are experiencing development of their level of self-efficacy.